Infants’ style of emotion regulation with their mothers and fathers: concordance between parents and the contribution of father–infant interaction quality - Martins, Eva Costa (2016)
The concordance between infants' emotion regulation styles with different partners has not been consistently analysed nor have the relational correlates of such potential across-partners similarities. We explored these issues by assessing 10-month-olds' (59.6 percent boys) emotion regulation styles separately with mother and father and by evaluating mother-infant and father-infant interaction quality. The sample consisted of 50 low-risk families. Two home visits were conducted and similar procedures were adopted for each visit. Parent-infant interaction quality was assessed during daily routines and during free play; both parents independently completed a temperament questionnaire. Infant emotion regulation was assessed in a semi-structured problem-solving task: adaptive vs. maladaptive (under and over-regulation) styles. As predicted, infants' emotion regulation with their mothers and fathers were related. However, only father-infant interaction quality predicted infants' emotion regulation concordance: lower interaction quality was associated with maladaptive concordance compared with non-concordance and higher interaction quality was associated with adaptive concordance compared with non-concordance. Our results support the claim that by the end of the first year of life, infants use similar emotion regulation styles with mother and father and point to father-infant interaction as an important correlate of emotion regulation across-parents.